Hot rolled steel plate

JP7667466B2Active Publication Date: 2025-04-23NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022575560
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-15
Filing Date
2022-01-07
Publication Date
2025-04-23
Estimated Expiration
2042-01-07

AI Technical Summary

Technical Problem

Existing hot rolled steel sheets with single-phase martensitic structures lack sufficient bending properties despite their high strength, as per the limitations observed in Patent Documents 1 and 2.

Method used

A hot rolled steel sheet with a chemical composition of specific elements in certain ranges and a metal structure comprising 90% or more of martensite and tempered martensite at 1/4 thickness, and 70-90% at 200 μm from the surface, along with controlled finishing rolling and cooling conditions.

Benefits of technology

The proposed solution achieves high strength and excellent bending properties in the hot rolled steel sheet, addressing the limitations of previous technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667466000001
    Figure 0007667466000001
  • Figure 0007667466000002
    Figure 0007667466000002
  • Figure 0007667466000003
    Figure 0007667466000003
Patent Text Reader

Abstract

With respect to this hot-rolled steel sheet, the metal structure contains, in an area ratio, a total of 90% or more of at least one of martensite and tempered martensite, and a total of 10% or less of at least one of ferrite, bainite and pearlite at 1 / 4 the sheet thickness, while containing, in an area ratio, a total of not less than 70% but less than 90% of at least one of martensite and tempered martensite, and a total of more than 10% but not more than 30% of at least one of ferrite, bainite and pearlite at the depth of 200 µm from the surface.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot-rolled steel sheet. This application claims priority based on Japanese Patent Application No. 2021-005008, filed on January 15, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, steel sheets have been made stronger to ensure the crashworthiness of automobiles and reduce the environmental impact. In order to increase the strength of steel sheets, it is effective to make the metal structure a martensite single phase. Steel sheets with a martensite single phase metal structure have poor ductility compared to dual phase steel sheets such as DP (Dual Phase) steel sheets and TRIP (Transformation Induced Plasticity) steel sheets, and are therefore often processed into the desired shape mainly by bending. For this reason, martensite single phase steel sheets are required to have excellent bendability.

[0003] Patent Document 1 discloses a high-strength hot-rolled steel sheet excellent in low-temperature toughness, characterized in having a structure in which a martensite phase or a tempered martensite phase is the main phase, the main phase occupies 90% or more by volume relative to the entire structure, the average grain size of prior austenite grains is 20 μm or less in a cross section parallel to the rolling direction and 15 μm or less in a cross section perpendicular to the rolling direction, and the aspect ratio of the prior austenite grains in a cross section parallel to the rolling direction is 18 or less.

[0004] Patent Document 2 discloses a high-strength hot-rolled steel sheet characterized in that the steel structure has a main phase consisting of at least one of a martensite phase and a tempered martensite phase and having an area ratio of 95% or more relative to the entire steel structure, contains cementite with an average grain size of 0.5 μm or less in the laths of the martensite phase and / or the tempered martensite phase, and the cementite content is 0.01 to 0.08% by mass.

[0005] However, the present inventors have found that the steel sheets described in Patent Documents 1 and 2 do not provide sufficient bendability. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 2016-211073 [Patent Document 2] Japanese Patent Application Publication No. 2018-188675 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a hot-rolled steel sheet having high strength and excellent bendability. [Means for solving the problem]

[0008] As a result of inventive investigation, the present inventors have obtained the following findings and arrived at the present invention. It has been discovered that a hot-rolled steel sheet having high strength and excellent bendability can be obtained by setting the total area ratio of martensite and tempered martensite to 90% or more in the metal structure at a position 1 / 4 of the plate thickness from the surface, and by setting the total area ratio of martensite and tempered martensite to 70% or more and less than 90% in the metal structure at a position 200 μm from the surface.

[0009] The present inventors have also found that in order to obtain the above-mentioned hot-rolled steel sheet, it is particularly effective to control the finish rolling conditions and the cooling conditions after the finish rolling.

[0010] The gist of the present invention, which has been made based on the above findings, is as follows. (1) A hot-rolled steel sheet according to one aspect of the present invention has a chemical composition, in mass%, C: 0.050~0.150%, Si: 0.01 to 1.00%, Mn: 1.00-2.50%, P: 0.100% or less, S: 0.020% or less, N: 0.0050% or less, Al: 0.001 to 0.300%, Ti: 0.001 to 0.100%, B: 0.0005~0.0050%, Nb: 0 to 0.100% Cr: 0-1.00%, V: 0 to 0.30%, Cu: 0-0.30%, Ni: 0 to 0.30%, and Ca: 0 to 0.0050%, with the remainder being Fe and impurities, Vc represented by the following formulas (1) to (3) is 10 to 40, The metal structure is, in area%, At 1 / 4 of the plate thickness, At least one of martensite and tempered martensite: 90% or more in total; and One or more of ferrite, bainite and pearlite: 10% or less in total; The average aspect ratio of prior austenite grains is 1.0 to 3.0; At a position 200 μm from the surface, One or more of martensite and tempered martensite: 70% or more and less than 90% in total; and One or more of ferrite, bainite and pearlite: the total amount is more than 10% and not more than 30%. When the effective B content is 0.0005 mass% or more, Vc=10 2.94-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) When the effective B content is less than 0.0005 mass%, Vc=10 3.69-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) (1) Effective B content = 10.81 × (B / 10.81 - dissolved N content / 14.01) (2) Solid solution N amount=14.01×(N / 14.01-Ti / 47.88) (3) However, each element symbol in the above formula (1) represents the content of the corresponding element in mass %, and 0 is substituted when the corresponding element is not contained. In the above formula (2), B is the content in mass % of B. When the effective B amount is a negative value, the effective B amount is regarded as 0. In the above formula (3), N and Ti are each expressed as a content in mass %. When the amount of solute N is a negative value, the amount of solute N is regarded as 0. (2) The hot-rolled steel sheet according to the above (1) has a chemical composition, in mass%, Nb: 0.005 to 0.100% Cr: 0.005~1.00%, V: 0.005~0.30%, Cu: 0.005-0.30%, Ni: 0.005 to 0.30%, and Ca: 0.0010~0.0050% The compound may contain one or more of the following: ( 3 )(1) above Or (2) In the hot-rolled steel sheet described in the above, the metal structure may have an average grain size of prior austenite grains of 5 to 40 μm at the 1 / 4 sheet thickness position. Effect of the Invention

[0011] According to the above-described aspects of the present invention, a hot-rolled steel sheet having high strength and excellent bendability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the hot-rolled steel sheet according to the present embodiment will be described in detail. However, the present invention is not limited to the configuration disclosed in the present embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0013] In the following, the numerical ranges indicated with "~" include the lower and upper limits. Values ​​indicated as "less than" and "more than" are not included in the numerical range. All "%" in chemical compositions refers to "% by mass".

[0014] The chemical composition of the hot-rolled steel sheet according to this embodiment contains, in mass%, C: 0.050-0.150%, Si: 0.01-1.00%, Mn: 1.00-2.50%, P: 0.100% or less, S: 0.020% or less, N: 0.0050% or less, Al: 0.001-0.300%, Ti: 0.001-0.100%, B: 0.0005-0.0050%, and the balance: Fe and impurities. Each element will be described below.

[0015] C: 0.050~0.150% C increases the strength of the hot-rolled steel sheet. If the C content is less than 0.050%, the desired strength cannot be obtained. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.070% or more. On the other hand, if the C content exceeds 0.150%, the weldability and toughness of the hot-rolled steel sheet are reduced. Therefore, the C content is set to 0.150% or less. The C content is preferably 0.130% or less or 0.110% or less.

[0016] Silicon: 0.01 to 1.00% Silicon increases the strength of hot-rolled steel sheets by improving solution strengthening and hardenability. Silicon also has a deoxidizing effect. If the Si content is less than 0.01%, the above effects cannot be obtained. Therefore, the Si content is set to 0.01% or more. On the other hand, if the Si content exceeds 1.00%, the ferrite transformation is promoted and the desired metal structure cannot be obtained. Therefore, the Si content is set to 1.00% or less. The Si content is preferably 0.40% or less or 0.30% or less.

[0017] Mn: 1.00-2.50% Mn increases the strength of the hot-rolled steel sheet by improving solution strengthening and hardenability. If the Mn content is less than 1.00%, the above effects cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.50% or more or 1.80% or more. On the other hand, if the Mn content exceeds 2.50%, the above effects are saturated. Therefore, the Mn content is set to 2.50% or less. The Mn content is preferably 2.30% or less or 2.20% or less.

[0018] P:0.100% or less P reduces the bendability of the hot-rolled steel sheet, so the P content is set to 0.100% or less, and preferably 0.020% or less. Since the lower the P content, the better, it is preferably 0%. However, since an excessive reduction in P increases the dephosphorization cost, the P content may be 0.001% or more.

[0019] S: 0.020% or less S reduces the bendability of a hot-rolled steel sheet, so the S content is set to 0.020% or less, and preferably 0.010% or less. The lower the S content, the better, so 0% is preferable. However, since excessive reduction in S increases the cost of desulfurization, the S content may be 0.001% or more.

[0020] N: 0.0050% or less N reduces the workability of a hot-rolled steel sheet, so the N content is set to 0.0050% or less, and preferably 0.0040% or less. Since the lower the N content, the better, it is preferably 0%. However, since excessive reduction in N increases the cost of denitrification, the N content may be 0.0010% or more.

[0021] Al: 0.001 to 0.300% Al has the effect of purifying steel by deoxidization (suppressing the occurrence of defects such as blowholes in steel). If the Al content is less than 0.001%, this effect cannot be obtained. Therefore, the Al content is set to 0.001% or more. The Al content is preferably 0.003% or more or 0.010% or more. On the other hand, if the Al content exceeds 0.300%, the above effect is saturated. In addition, the ferrite transformation is promoted, and the desired metal structure cannot be obtained. Therefore, the Al content is set to 0.300% or less. The Al content is preferably 0.100% or less or 0.050% or less.

[0022] Ti: 0.001 to 0.100% Ti increases the strength of the hot-rolled steel sheet by finely precipitating in the steel sheet as carbides. Ti also fixes N by forming nitrides and inhibits coarsening of austenite grains. If the Ti content is less than 0.001%, the above effects cannot be obtained. In addition, the metal structure at a position 200 μm from the surface cannot be favorably controlled, and desired bendability cannot be obtained. Therefore, the Ti content is set to 0.001% or more. The Ti content is preferably 0.005% or more or 0.010% or more. On the other hand, if the Ti content exceeds 0.100%, a large amount of coarse carbides and nitrides precipitate in the steel, which reduces the workability of the hot-rolled steel sheet. Therefore, the Ti content is set to 0.100% or less. The Ti content is preferably 0.050% or less or 0.030% or less.

[0023] B: 0.0005~0.0050% B segregates at the austenite grain boundaries and significantly improves the hardenability even at a small content, thereby increasing the strength of the hot-rolled steel sheet. If the B content is less than 0.0005%, the above effect cannot be obtained. Therefore, the B content is set to 0.0005% or more. The B content is preferably 0.0010% or more or 0.0013% or more. On the other hand, if the B content exceeds 0.0050%, the recrystallization of austenite during hot rolling is suppressed, the rolling load increases, and the desired metal structure cannot be obtained. Therefore, the B content is set to 0.0050% or less. The B content is preferably 0.0040% or less or 0.0030% or less.

[0024] The balance of the chemical composition of the hot-rolled steel sheet according to the present embodiment may be Fe and impurities. In the present embodiment, the impurities are those mixed in from raw materials such as ore, scrap, or the manufacturing environment. And means that it is permissible within a range that does not adversely affect the hot-rolled steel sheet according to this embodiment.

[0025] The hot-rolled steel sheet according to the present embodiment may contain the following optional elements instead of a part of Fe. When the optional elements are not contained, the lower limit of the content is 0%. Each optional element will be described below.

[0026] Nb: 0.005 to 0.100% Nb precipitates in steel as carbides or nitrides, increasing the strength of hot-rolled steel sheets. These precipitates also suppress the coarsening of austenite grains and promote the refinement of the metal structure. To reliably obtain these effects, the Nb content is preferably 0.005% or more. On the other hand, if the Nb content exceeds 0.100%, a large amount of coarse carbides and nitrides precipitate in the steel, which reduces the workability of the hot-rolled steel sheet. Therefore, the Nb content is set to 0.100% or less. Preferably, the Nb content is set to 0.030% or less.

[0027] Cr: 0.005~1.00% Cr improves the hardenability and increases the strength of the hot-rolled steel sheet. To reliably obtain this effect, the Cr content is preferably 0.005% or more. On the other hand, if the Cr content exceeds 1.00%, the weldability of the hot-rolled steel sheet decreases, so the Cr content is set to 1.00% or less, and preferably 0.30% or less.

[0028] V: 0.005~0.30% V contributes to increasing the strength of the hot-rolled steel sheet by dissolving in steel, and also contributes to increasing the strength of the hot-rolled steel sheet by precipitating in the steel sheet as carbides, nitrides, or carbonitrides, thereby enhancing precipitation strengthening. To reliably obtain these effects, the V content is preferably 0.005% or more. On the other hand, if the V content exceeds 0.30%, the toughness of the hot-rolled steel sheet decreases, so the V content is set to 0.30% or less, and preferably 0.10% or less.

[0029] Cu: 0.005~0.30% Cu dissolves in steel and contributes to increasing the strength of the hot-rolled steel sheet, and also contributes to improving the corrosion resistance. In order to reliably obtain these effects, the Cu content is preferably 0.005% or more. On the other hand, if the Cu content exceeds 0.30%, the surface properties of the hot-rolled steel sheet deteriorate, so the Cu content is set to 0.30% or less, and preferably 0.10% or less.

[0030] Ni: 0.005~0.30% Ni dissolves in steel and contributes to increasing the strength of the hot-rolled steel sheet, and also contributes to improving the toughness. In order to reliably obtain these effects, the Ni content is preferably 0.005% or more. Ni is an expensive element, and even if the Ni content exceeds 0.30%, it causes an increase in alloy cost. Therefore, the Ni content is set to 0.30% or less. The Ni content is preferably 0.10% or less.

[0031] Ca: 0.0010~0.0050% Ca refines oxides and nitrides that precipitate during solidification, improving the cleanliness of steel ingots or steel slabs. To reliably obtain this effect, the Ca content is preferably 0.0010% or more. On the other hand, even if the Ca content exceeds 0.0050%, the above effects are saturated and the cost increases. Therefore, the Ca content is set to 0.0050% or less. The Ca content is preferably 0.0030% or less.

[0032] The chemical composition of hot-rolled steel sheets may be measured by a general analytical method, such as inductively coupled plasma-atomic emission spectrometry (ICP-AES) or optical emission spectroscopy (OES). C and S may be measured using the combustion-infrared absorption method, and N may be measured using the inert gas fusion-thermal conductivity method.

[0033] The chemical composition of the hot-rolled steel sheet according to this embodiment has a Vc represented by the following formulas (1) to (3) of 10 to 40. If Vc is less than 10 or exceeds 40, the metal structure cannot be preferably controlled at the 1 / 4 sheet thickness position and / or at a position 200 μm from the surface.

[0034] The effective B amount in the following formula (1) is the amount of B that contributes to hardenability and can be obtained by the following formula (2). The amount of solute N in the following formula (2) can be obtained by the following formula (3).

[0035] When effective B content is 0.0005 mass% or more Vc=10 2.94-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) When effective B content is less than 0.0005% by mass Vc=10 3.69-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) (1) Effective B content = 10.81 × (B / 10.81 - dissolved N content / 14.01) (2) Solid solution N amount=14.01×(N / 14.01-Ti / 47.88) (3) Each element symbol in the above formula (1) represents the content of the corresponding element in mass %, and 0 is substituted when the corresponding element is not contained. In the above formula (2), B is the content in mass % of B. When the effective B amount is a negative value, the effective B amount is regarded as 0. In the above formula (3), N and Ti are each expressed as a content in mass %. When the amount of solute N is a negative value, the amount of solute N is regarded as 0.

[0036] Next, the metal structure of the hot-rolled steel sheet according to this embodiment will be described. The hot-rolled steel sheet according to this embodiment has a metal structure, in terms of area%, At 1 / 4 of the plate thickness, At least one of martensite and tempered martensite: 90% or more in total; and One or more of ferrite, bainite and pearlite: 10% or less in total; At a position 200 μm from the surface, One or more of martensite and tempered martensite: 70% or more and less than 90% in total; and One or more of ferrite, bainite and pearlite: the total amount is more than 10% and not more than 30%. Each provision will be explained in detail below.

[0037] Plate thickness 1 / 4 position In this embodiment, the 1 / 4 thickness position specifically refers to a region 10 μm from the 1 / 4 thickness position on both sides, that is, a region from a position of 1 / 4-10 μm thickness from the surface to a position of 1 / 4+10 μm thickness from the surface. In other words, the region starts at a position of 1 / 4-10 μm thickness from the surface and ends at a position of 1 / 4+10 μm thickness from the surface.

[0038] At least one of martensite and tempered martensite: 90% or more in total Martensite and tempered martensite are hard, homogeneous and fine structures. By including these structures, high strength can be obtained. If the total area ratio of these structures is less than 90%, the desired strength cannot be obtained. Therefore, the total area ratio of these structures is set to 90% or more. It is not necessary to include both martensite and tempered martensite, and even if only one of them is included, it is sufficient that the area ratio is 90% or more. The total area ratio of martensite and tempered martensite is preferably 92% or more or 95% or more. It is more preferably 100%.

[0039] One or more of ferrite, bainite and pearlite: 10% or less in total The hot-rolled steel sheet according to this embodiment may contain ferrite, bainite, and pearlite as the remaining structure other than martensite and tempered martensite in the metal structure at the 1 / 4 position of the sheet thickness. If the total area ratio of these exceeds 10%, the strength of the hot-rolled steel sheet decreases. Therefore, the total area ratio of ferrite, bainite, and pearlite is set to 10% or less, preferably 8% or less, 5% or less, and more preferably 0%. It is not necessary for the steel sheet to contain all of ferrite, bainite and pearlite.

[0040] 200μm from the surface In this embodiment, the position 200 μm from the surface specifically refers to a region 10 μm from the "position 200 μm from the surface," that is, a position 200 μm-10 μm (190 μm) from the surface to a position 200 μm+10 μm (210 μm) from the surface. In other words, the region starts at a position 190 μm from the surface in the sheet thickness direction and ends at a position 210 μm from the surface in the sheet thickness direction.

[0041] Martensite and / or tempered martensite: 70% or more, but less than 90% in total As described above, martensite and tempered martensite are hard, homogeneous and fine structures. These structures are suitable for obtaining high strength, but are inferior in bendability. In the hot-rolled steel sheet according to the present embodiment, in order to obtain the desired bendability, the area ratio of martensite and tempered martensite at a position 200 μm from the surface is made smaller than the area ratio of martensite and tempered martensite at a position 1 / 4 of the sheet thickness. If the total area ratio of martensite and tempered martensite at a position 200 μm from the surface is 90% or more, the bendability of the hot-rolled steel sheet is deteriorated. Therefore, the total area ratio of these structures is made less than 90%. It is preferably 87% or less or 85% or less. If the total area ratio of martensite and tempered martensite is less than 70%, the desired strength cannot be obtained, so the total area ratio of these structures is set to 70% or more, preferably 75% or more. In addition, the difference between the sum of martensite and tempered martensite at 1 / 4 of the sheet thickness and the sum of the area ratios of martensite and tempered martensite at 200 μm from the surface (= "sum of martensite and tempered martensite at 1 / 4 of the sheet thickness" - "sum of the area ratios of martensite and tempered martensite at 200 μm from the surface") is preferably 5% or more, more preferably 10% or more or 15% or more.

[0042] It is not necessary that both martensite and tempered martensite are contained. Even if only one of them is contained, it is sufficient that the area ratio thereof is 70% or more and less than 90%.

[0043] One or more of ferrite, bainite and pearlite: more than 10% and less than 30% The hot-rolled steel sheet according to the present embodiment may contain ferrite, bainite and pearlite as the remaining structure other than martensite and tempered martensite in the metal structure at a position 200 μm from the surface. These structures are inferior in strength but excellent in bendability. If the total area ratio of these structures is 10% or less, excellent bendability cannot be obtained. Therefore, the total area ratio of these structures is made to be more than 10%, and is preferably 15% or more. It is not necessary to contain all of ferrite, bainite and pearlite, and even if only one of them is contained, it is sufficient that the content is more than 10%. Furthermore, if the total area ratio of these structures exceeds 30%, the desired strength cannot be obtained, so the total area ratio of these structures is set to 30% or less, preferably 25% or less.

[0044] In this embodiment, in addition to the metal structure at the 1 / 4 sheet thickness position and the metal structure at the position 200 μm from the surface, the metal structure at the position 100 μm from the surface may be controlled. The metal structure at a position 100 μm from the surface preferably contains at least one of martensite and tempered martensite: 60 to 80% in total, and at least one of ferrite, bainite and pearlite: 20 to 40% in total.

[0045] 100μm from the surface In this embodiment, the position 100 μm from the surface specifically refers to a region 10 μm from the "position 100 μm from the surface," that is, a position 100 μm-10 μm (90 μm) from the surface to a position 100 μm+10 μm (110 μm) from the surface. In other words, it is a region starting from a position 90 μm from the surface in the sheet thickness direction and ending at a position 110 μm from the surface in the sheet thickness direction.

[0046] Martensite and / or tempered martensite: 60-80% in total By setting the total area ratio of martensite and tempered martensite to 80% or less, the bendability of the hot-rolled steel sheet can be improved, and therefore, it is preferable that the total area ratio of these structures is set to 80% or less. By making the total area ratio of martensite and tempered martensite 60% or more, the strength can be increased, and therefore it is preferable that the total area ratio of these structures is 60% or more.

[0047] It is not necessary that both martensite and tempered martensite are contained. Even if only one of them is contained, it is sufficient that the area ratio thereof is 60 to 80%.

[0048] One or more of ferrite, bainite and pearlite: 20-40% in total The hot-rolled steel sheet according to the present embodiment may contain ferrite, bainite and pearlite as the remaining structure other than martensite and tempered martensite in the metal structure at a position 100 μm from the surface. By making the total area ratio of these structures 20% or more, the bendability can be improved. Therefore, it is preferable that the total area ratio of these structures is 20% or more. It is not necessary to contain all of ferrite, bainite and pearlite, and even if only one of them is contained, it is sufficient that the content is 20% or more. Moreover, by setting the total area ratio of these structures to 40% or less, the strength can be increased, and therefore it is preferable that the total area ratio of these structures be set to 40% or less.

[0049] The method for measuring the area ratio of each texture will be described below. Test pieces are taken from the hot-rolled steel sheet in a cross section parallel to the rolling direction so that the metal structure can be observed at positions 100 μm from the surface, 200 μm from the surface, and 1 / 4 of the sheet thickness from the surface.

[0050] The cross section of the above test piece is polished using #600 to #1500 silicon carbide paper, and then finished to a mirror surface using a liquid in which diamond powder with a grain size of 1 to 6 μm is dispersed in a diluent such as alcohol or pure water. Next, the sample is polished using colloidal silica that does not contain an alkaline solution at room temperature to remove the strain introduced into the surface layer of the sample. At any position in the longitudinal direction of the sample cross section, 150 μm in the rolling direction x 20 μm in the plate thickness direction is measured using electron backscatter diffraction at measurement intervals of 0.1 μm to obtain crystal orientation information.

[0051] For the measurements, an EBSD analyzer consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSD detector (TSL DVC5 detector) was used. The vacuum level in the EBSD analyzer was 9.6×10 -5The conditions are: 1. 2 Pa or less, acceleration voltage is 15 kV, irradiation current level is 13, and electron beam irradiation level is 62. The obtained crystal orientation information is used with the "Phase Map" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device to determine whether the crystal structure is bcc, bainite, ferrite, or "pearlite, martensite, and tempered martensite."

[0052] For these regions, the "Grain Orientation Spread" function installed in the "OIM Analysis (registered trademark)" software attached to the EBSD analysis device is used to extract regions with a "Grain Orientation Spread" of 1° or less as ferrite under the condition that the 15° grain boundary is defined as the grain boundary. The area ratio of the extracted ferrite is calculated to obtain the area ratio of ferrite.

[0053] Next, within the remaining region (region where "Grain Orientation Spread" exceeds 1°), under the condition that the 5° grain boundary is defined as the crystal grain boundary, when the maximum value of "Grain Average IQ" in the ferrite region is Iα, the region exceeding Iα / 2 is extracted as bainite, and the region where it is Iα / 2 or less is extracted as "pearlite, martensite and tempered martensite." The area ratio of bainite is obtained by calculating the area ratio of the extracted bainite.

[0054] Regarding the above extracted "pearlite, martensite, and tempered martensite," pearlite, martensite, and tempered martensite can be distinguished by the following method. First, in order to observe the same area as the EBSD measurement area with an SEM, a Vickers indentation is made near the observation position. After that, the surface contamination is polished away, leaving the structure of the observation surface, and the surface is etched with nital. Next, the same field of view as the EBSD observation surface is observed with an SEM at a magnification of 3000x.

[0055] In the EBSD measurement, among the regions judged as "pearlite, martensite, and tempered martensite," the regions that have a substructure within the grains and in which cementite precipitates with multiple variants are judged to be tempered martensite. The region where cementite precipitates in a lamellar form is determined to be pearlite. Areas with high brightness and where the underlying structure has not been revealed by etching are judged to be martensite. By calculating the area ratio of each, the area ratios of tempered martensite, pearlite, and martensite are obtained.

[0056] Contamination on the surface of the observation surface can be removed by buffing using alumina particles with a particle size of 0.1 μm or less, or by Ar ion sputtering or other methods. The above-mentioned measurement is performed at a position 100 μm from the surface, a position 200 μm from the surface, and a position 1 / 4 of the plate thickness from the surface, to obtain the area ratio of the metal structure at each position.

[0057] In the hot-rolled steel sheet according to this embodiment, the average aspect ratio of prior austenite grains in the metal structure at the 1 / 4 position of the sheet thickness is preferably 1.0 to 3.0. In addition, in the metal structure at the 1 / 4 position of the sheet thickness, the average grain size of prior austenite grains is preferably 5 to 40 μm.

[0058] Average aspect ratio of prior austenite grains: 1.0 to 3.0 By setting the average aspect ratio of prior austenite grains in the metal structure at the 1 / 4 position of the sheet thickness to 1.0 to 3.0, anisotropy in properties can be reduced, and as a result, the bendability of the hot-rolled steel sheet can be further improved. The aspect ratio of a prior austenite grain is the value obtained by dividing the major axis of the prior austenite grain by the minor axis, and takes a value of 1.0 or more. The smaller the aspect ratio, the more equiaxed the crystal grain is, and the larger the aspect ratio, the more flat the crystal grain is. The aspect ratio is an index that indicates the degree of anisotropy of properties.

[0059] Average grain size of prior austenite grains: 5~40μm In the metal structure at the 1 / 4 position of the sheet thickness, by setting the average grain size of the prior austenite grains to 5 to 40 μm, the bendability can be further improved.

[0060] The method for measuring the average aspect ratio and average grain size of prior austenite grains at the 1 / 4 position of the sheet thickness will be described below. A test piece is taken from a hot-rolled steel sheet so that the metal structure can be observed at a position 1 / 4 of the sheet thickness from the surface on a cross section parallel to the rolling direction. The observation surface is corroded with a saturated aqueous solution of picric acid to reveal the prior austenite grain boundaries. Enlarged photographs of the corroded cross section parallel to the rolling direction at a position 1 / 4 of the sheet thickness from the surface are taken using a scanning electron microscope (SEM) at a magnification of 1000 times, with a field of view of 100 μm × 100 μm for 5 or more fields. At least 20 prior austenite grains with a circle equivalent diameter (diameter) of 2 μm or more contained in each SEM photograph are obtained by image processing. The average value of these is calculated to obtain the average grain size of the prior austenite grains. If prior austenite grains with a circle equivalent diameter of less than 2 μm are included, these are excluded from the above measurement.

[0061] In addition, the long and short axes of at least 20 prior austenite grains having a circle equivalent diameter (diameter) of 2 μm or more contained in each of the above SEM photographs are measured. The average long and short axes of the prior austenite grains are obtained by calculating the average values ​​of the long and short axes measured for each prior austenite grain. The average aspect ratio of the prior austenite grains is obtained by calculating the ratio of these (average long axis / average short axis).

[0062] Tensile strength: 980MPa or more The hot-rolled steel sheet according to the present embodiment may have a tensile (maximum) strength of 980 MPa or more. By making the tensile strength 980 MPa or more, the applicable parts are not limited, and the contribution to the weight reduction of the vehicle body can be increased. More preferably, the tensile strength is 1000 MPa or more, 1100 MPa or more. The upper limit does not need to be particularly set, but may be set to 1470 MPa from the viewpoint of suppressing die wear.

[0063] The tensile strength is measured in accordance with JIS Z 2241: 2011 using a No. 5 test piece of JIS Z 2241: 2011. The position where the tensile test piece is taken is the center position in the sheet width direction, and the direction perpendicular to the rolling direction is the longitudinal direction.

[0064] R / t: 1.5 or less The hot-rolled steel sheet according to the present embodiment may have a ratio R / t of the limit bending radius R to the sheet thickness t, which is obtained by a test based on the V-block method described later, of 1.5 or less. If R / t is 1.5 or less, it can be determined that the hot-rolled steel sheet has excellent bendability.

[0065] R / t can be obtained in the following way. Cut out a 100mm x 30mm rectangular test piece from the half-width position of the hot-rolled steel sheet. For bending where the bending ridgeline is parallel to the rolling direction (L direction) (L-axis bending), perform a test in accordance with the V-block method of JIS Z 2248:2006 (bending angle θ is 90°). Find the minimum bending radius R at which no cracks occur, and divide by the sheet thickness t to obtain the limit bending R / t.

[0066] However, to determine the presence or absence of cracks, the bent surface of the test piece after the V-block 90° bending test is observed with a magnifying glass or optical microscope at a magnification of 10x or more, and if the length of the crack observed on the bent surface of the test piece exceeds 0.5 mm, it is determined that a crack is present.

[0067] Plate thickness: more than 0.8mm, less than 8.0mm The thickness of the hot-rolled steel sheet according to the present embodiment is not particularly limited, but may be more than 0.8 mm and 8.0 mm or less. If the thickness of the hot-rolled steel sheet is 0.8 mm or less, it may be difficult to ensure the rolling completion temperature and the rolling load may become excessive, making hot rolling difficult. Therefore, the thickness of the hot-rolled steel sheet according to the present embodiment may be more than 0.8 mm. It is preferably 1.2 mm or more, or 1.4 mm or more. On the other hand, if the sheet thickness exceeds 8.0 mm, it may be difficult to obtain the above-mentioned metal structure. Therefore, the sheet thickness may be 8.0 mm or less, and is preferably 6.0 mm or less.

[0068] Plating layer The hot-rolled steel sheet according to the present embodiment having the above-mentioned chemical composition and metal structure may be provided with a plating layer on the surface for the purpose of improving corrosion resistance, etc., to form a surface-treated steel sheet. The plating layer may be an electroplating layer or a hot-dip plating layer. Examples of the electroplating layer include electrogalvanizing and electrogalvanizing Zn-Ni alloy plating. Examples of the hot-dip plating layer include hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip aluminum plating, hot-dip Zn-Al alloy plating, hot-dip Zn-Al-Mg alloy plating, and hot-dip Zn-Al-Mg-Si alloy plating. The coating weight is not particularly limited and may be the same as in the past. In addition, it is also possible to further improve the corrosion resistance by performing an appropriate chemical conversion treatment (for example, application of a silicate-based chromium-free chemical conversion treatment liquid and drying) after plating.

[0069] Next, a preferred method for producing the hot-rolled steel sheet according to the present embodiment will be described. Note that the temperature of the slab and the temperature of the steel sheet in the present embodiment refer to the surface temperature of the slab and the surface temperature of the steel sheet.

[0070] A preferred method for producing a hot-rolled steel sheet according to this embodiment includes the following steps. A slab having the above-mentioned chemical composition is heated to a temperature range of 1100 to 1250°C. Rough rolling is performed so that the rough rolling completion temperature is 1000 to 1100°C. Finish rolling is carried out so as to satisfy the following conditions. (I) The tension of the steel plate between the final pass and the pass before the final pass is 2.0 to 5.0 kg / mm 2 It is. (II) The finish rolling completion temperature FT is Ac3 point + 10°C to Ac3 point + 30°C. (III) The reduction ratio of the final pass is 20 to 40%. Cooling is performed so that the average cooling rate in the temperature range from the finish rolling completion temperature FT to the Ms point is Vc+10°C / s to Vc+40°C / s. Cooling is stopped in the temperature range of Ms point -200℃ or less, and then the wire is wound. However, in the finish rolling, it is more preferable to satisfy the condition (IV) that the cumulative rolling reduction is 75 to 95%. Each step will be described in detail below.

[0071] Slab heating temperature: 1100~1250℃ It is preferable to heat the slab having the above-mentioned chemical composition to a temperature range of 1100 to 1250°C. If the heating temperature of the slab is less than 1100°C, the deformation resistance during hot rolling may be high, and the rolling load may increase. Therefore, the heating temperature is preferably 1100°C or higher. On the other hand, if the heating temperature exceeds 1250° C., prior austenite grains may become coarse and the low-temperature toughness of the hot-rolled steel sheet may decrease. Therefore, the heating temperature is preferably 1250° C. or less.

[0072] From the viewpoint of production costs, the slab to be heated is preferably produced by continuous casting, but may be produced by other casting methods (for example, an ingot casting method).

[0073] Rough rolling completion temperature: 1000~1100℃ Hot rolling is roughly divided into rough rolling and finish rolling. In order to make the slab into a rough bar of the desired size and shape and to easily adjust the finish rolling completion temperature within a desired range, it is preferable to perform rough rolling so that the rough rolling completion temperature is 1000 to 1100°C.

[0074] Finish rolling (I) Steel plate tension between the final pass and the pass before the final pass: 2.0 to 5.0 kg / mm 2 In the finish rolling, the tension of the steel plate between the final pass and the pass before the final pass is set to 2.0 kg / mm 2By setting the tension to 5.0 kg / mm ​​or more, favorable friction occurs between the rolling roll and the surface layer region of the steel sheet, and a load shear strain can be introduced into the surface layer region. As a result, a desired metal structure can be obtained at a position 200 μm from the surface. 2 If the rolling strength exceeds 100%, the steel sheet may break and the finish rolling may not be performed stably.

[0075] The tension of the steel sheet may be adjusted by increasing the rotation speed of the final pass and / or the pass one pass before the final pass, Looper It may be adjusted by increasing

[0076] (II) Finish rolling completion temperature FT: Ac3 points +10℃~Ac3 points +30℃ By setting the finish rolling completion temperature FT to Ac3 point + 10°C or higher, it is possible to suppress the formation of a large amount of ferrite and bainite at a position 200 μm from the surface, and as a result, it is possible to obtain the desired amount of martensite and tempered martensite. In addition, by setting the finish rolling completion temperature FT to Ac3 point + 30°C or lower, it is possible to suppress the release of strain in the surface layer region imparted under rolling in the final pass of finish rolling. As a result, it is possible to suppress the amount of martensite at a position 200 μm from the surface from becoming excessive.

[0077] In this embodiment, the Ac3 point is represented by the following formula. Ac3=937.2-436.5×C+56×Si-19.7×Mn-16.3×Cu-26.6×Ni-4.9×Cr+124.8×V+136.3×Ti-19.1×Nb+198.4×Al+3315×B Each element symbol in the above formula indicates the content of the corresponding element in mass %, and 0 is substituted when the element is not contained.

[0078] (III) Reduction rate of final pass: 20-40% In order to obtain a desired amount of martensite at a position 200 μm from the surface, the reduction ratio of the final pass is preferably set to 20 to 40%. By setting the reduction ratio to 20% or more, the amount of strain introduced into the surface layer region is not insufficient, and a sufficient driving force for the ferrite, bainite, and pearlite transformations can be secured. In addition, by setting the reduction ratio to 40% or less, the driving force for the ferrite, bainite, and pearlite transformations can be prevented from becoming excessive. As a result, the metal structure at a position 200 μm from the surface can be preferably controlled.

[0079] The reduction ratio of the final pass of finish rolling is obtained by dividing the thickness t0 of the steel plate before the final pass by the thickness t1 of the steel plate after the final pass ((1-t0 / t1) x 100).

[0080] (IV) Cumulative reduction rate: 75~95% This condition is more preferable. The cumulative reduction in the finish rolling is the thickness of the steel plate before the finish rolling, t i The thickness of the steel plate after finishing rolling is t f Divide by ((1-t i / t f )×100). By setting the cumulative reduction rate of the finish rolling to 75 to 95%, the average grain size and average aspect ratio of the prior austenite grains can be suitably controlled.

[0081] Average cooling rate in the temperature range of finish rolling completion temperature FT~Ms point: Vc+10℃ / s~Vc+40℃ / s After the finish rolling is completed, the steel sheet is cooled by water cooling to a temperature range where austenite transforms into martensite, thereby obtaining a desired metal structure. If the average cooling rate is too slow, ferrite and / or bainite may be generated during the cooling process, and the strength of the hot-rolled steel sheet may decrease. Therefore, the average cooling rate in the temperature range from the finish rolling completion temperature FT to the Ms point is preferably Vc+10°C / s or more. If the average cooling rate is too fast, the desired amount of martensite may not be obtained in the surface layer region. As a result, excellent bendability may not be obtained. As a result, the metal structure at a position 200 μm from the surface may not be controlled in a favorable manner. Therefore, the average cooling rate in the temperature range from the finish rolling completion temperature FT to the Ms point is set to Vc+40°C / s or less. The water cooling at the above average cooling rate is preferably carried out up to a cooling stop temperature described below.

[0082] The average cooling rate here is defined as the temperature difference between the start point and the end point of the set range divided by the elapsed time from the start point to the end point. It should be noted that Vc is expressed by the above formulas (1) to (3).

[0083] The Ms point is expressed by the following formula. Ms = 561-474 x C-33 x Mn-17 x Ni Each element symbol in the above formula indicates the content of the corresponding element in mass %, and 0 is substituted when the element is not contained.

[0084] Cooling stop temperature (winding temperature): Ms point -200℃ or less The cooling end temperature is preferably Ms point −200° C. or lower, more preferably Ms point −250° C. or lower, and even more preferably Ms point −300° C. or lower. After cooling is stopped, coiling is performed. The lower limit of the cooling stop temperature is not particularly limited, but may be room temperature (25° C.).

[0085] The hot-rolled steel sheet according to the present embodiment can be manufactured by the method described above. If necessary, the above-mentioned plating layer may be formed on the surface of the hot-rolled steel sheet. EXAMPLES

[0086] Slabs having the chemical compositions shown in Tables 1A and 1B were produced by continuous casting. The obtained slabs were used to produce hot-rolled steel sheets shown in Tables 3A and 3B under the conditions shown in Tables 2A and 2B. After cooling to the cooling stop temperatures shown in Tables 2A and 2B, the sheets were immediately coiled.

[0087] The metal structure, tensile strength, and R / t of the obtained hot-rolled steel sheets were measured at the 1 / 4 sheet thickness position, the 200 μm position from the surface, and the 100 μm position from the surface by the above-mentioned method. In addition, the total elongation (%) was obtained from the tensile test performed by the above-mentioned method. The results are shown in Tables 3A and 3B. The steel sheet tension indicates the steel sheet tension between the final pass and the pass one pass before the final pass. M indicates martensite, TM indicates tempered martensite, F indicates ferrite, B indicates bainite, and P indicates pearlite. In some cases, the formation of large amounts of ferrite, bainite, and pearlite made the morphology of the prior austenite grains unclear, and therefore it was not possible to measure the average aspect ratio and average grain size of the prior austenite grains at the 1 / 4 position of the sheet thickness.

[0088] When the tensile strength was 980 MPa or more, it was judged to have high strength and to pass the test, whereas when the tensile strength was less than 980 MPa, it was judged to have poor strength and to fail the test. When R / t was 1.5 or less, the specimen was judged to have excellent bendability and to pass the test, whereas when R / t was more than 1.5, the specimen was judged to have poor bendability and to fail the test. When the total elongation was 8.5% or more, it was judged to be excellent in ductility and to pass the test.

[0089] [Table 1A]

[0090] [Table 1B]

[0091] [Table 2A]

[0092] [Table 2B]

[0093] [Table 3A]

[0094] [Table 3B]

[0095] It can be seen from Tables 3A and 3B that the hot-rolled steel sheets according to the examples of the present invention have high strength and excellent bendability. On the other hand, it is found that the hot-rolled steel sheets according to the comparative examples are inferior in at least one of the above properties. [Industrial Applicability]

[0096] According to the above-described aspects of the present invention, a hot-rolled steel sheet having high strength and excellent bendability can be provided.

Claims

1. The chemical composition, in mass%, is C: 0.050-0.150%, Si: 0.01-1.00%, Mn: 1.00-2.50%, P: 0.100% or less, S: 0.020% or less, N: 0.0050% or less, Al: 0.001-0.300%, Ti: 0.001 to 0.100%, B: 0.0005 to 0.0050%, Nb: 0-0.100% Cr: 0-1.00%, V: 0 to 0.30%, Cu: 0 to 0.30%, Ni: 0 to 0.30%, and Ca: 0-0.0050%, with the remainder being Fe and impurities, Vc represented by the following formulas (1) to (3) is 10 to 40, The metal structure is, in area percent, At the 1 / 4 plate thickness position, One or more of martensite and tempered martensite: 90% or more in total; and One or more of ferrite, bainite, and pearlite: 10% or less in total; The average aspect ratio of prior austenite grains is 1.0 to 3.0; At a position 200 μm from the surface, One or more of martensite and tempered martensite: 70% or more and less than 90% in total; and One or more of ferrite, bainite, and pearlite: a total content of more than 10% and not more than 30% A hot-rolled steel sheet characterized by: When the effective B content is ≧0.0005 mass%, Vc=10 2.94-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) When the effective B content is less than 0.0005 mass%, Vc=10 3.69-0.75×(2.7×C+0.4×Si+Mn+0.45×Ni+0.8×Cr) (1) Effective B content = 10.81 × (B / 10.81 - dissolved N content / 14.01) (2) Solid solution N amount = 14.01×(N / 14.01-Ti / 47.88) (3) However, each element symbol in the above formula (1) represents the content of the corresponding element in mass %, and 0 is substituted when the corresponding element is not contained. In the above formula (2), B is the content in mass % of B. When the effective B amount is a negative value, the effective B amount is set to 0. In the above formula (3), N and Ti are each a content in mass %. When the amount of solute N is a negative value, the amount of solute N is regarded as zero.

2. The chemical composition, in mass%, Nb: 0.005-0.100% Cr: 0.005-1.00%, V: 0.005-0.30%, Cu: 0.005-0.30%, Ni: 0.005 to 0.30%, and Ca: 0.0010-0.0050% The hot-rolled steel sheet according to claim 1, further comprising one or more of the group consisting of:

3. The metal structure at the plate thickness 1 / 4 position, The hot-rolled steel sheet according to claim 1 or 2, characterized in that the prior austenite grains have an average grain size of 5 to 40 μm.

Citation Information

Patent Citations

  • High-strength hot-rolled steel sheet having excellent bendability and low-temperature toughness and method for manufacturing same

    EP3730647A1

  • High strength hot rolled steel sheet and production method therefor

    JP2016211073A

  • High strength hot-rolled steel sheet and production method thereof

    JP2018188675A

  • High-strength hot-rolled steel sheet and method for manufacturing same

    WO2020026593A1

  • Hot-rolled steel strip & manufacturing method

    WO2020099473A1